2019
DOI: 10.30736/jesa.v4i2.63
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Efisiensi Kinerja Lembaga Amil Zakat Di Indonesia

Abstract: In the span of 74 years of Indonesia's independence, poverty, unemployment and social inequality remain major problems in national development. The Central Statistics Agency (BPS) recorded that as of March 2018, the number of poor people in Indonesia reached 25.95 million people or 9.82 percent of the total population of Indonesia. Seeing the problems that are so complex, it should be to pay attention to one solution in Islam to be able to prosper the community. Islam as rahmatan li al-‘a>lami>n has a so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
1
5
0
1
Order By: Relevance
“…The results of Dompet Duafa's efficiency is the same for the decreasing conditions in 2015 and 2016 in Fathurrahman & Hajar (2019) study. The difference in results occurred in 2012-2014, and different conditions also occurred in Parisi (2017) findings between 2010-2013 with IRS, while this study showed decreasing conditions.…”
Section: Dompet Dhuafasupporting
confidence: 52%
See 1 more Smart Citation
“…The results of Dompet Duafa's efficiency is the same for the decreasing conditions in 2015 and 2016 in Fathurrahman & Hajar (2019) study. The difference in results occurred in 2012-2014, and different conditions also occurred in Parisi (2017) findings between 2010-2013 with IRS, while this study showed decreasing conditions.…”
Section: Dompet Dhuafasupporting
confidence: 52%
“…Also, zakat institutions can be considered sound, credible, effective, and proficient when they meet several performance indicators. This performance refers to the objectives and activities in accordance with the needs of the community (Fathurrahman & Hajar, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of the depth of poverty, it was found that the zakat intervention was able to reduce the severity of poverty by 12.12-15.97 percent. Zakat can reduce the number of low-income families from 84 percent to 74 percent [1]. Then from the aspect of the depth of poverty, zakat is also proven to reduce the poverty gap and income gap.…”
Section: Introductionmentioning
confidence: 99%
“…Bila sebuah lembaga menjalankan aktivitas tanpa melakukan pengukuran terhadap kinerja, maka lembaga tersebut tidak dapat melakukan perbaikan, meningkatkan pelayanannya, melakukan efisiensi, maupun memberikan perlakuan yang tepat kepada karyawannya (Gozali, 2005) Ukuran-ukuran efisiensi organisasi nirlaba seperti BAZ/LAZ adalah sebagai berikut (Fathurrahman & Hajar, 2019): Benefit, menyatakan ukuran keuangan dari nilai sosial yang dilekatkan pada jasa organisasi. Penilaian keuangan dari benefit mencakup dua komponen yaitu, pengeluaran sosial dan peningkatan pendapatan masyarakat (dalam lembaga amil zakat yang dimaksud masyarakat adalah mustahik).…”
Section: Pengukuran Efisiensi Pada Organisasi Pengelola Zakat (Opz)unclassified